O ensino da ética em cursos de computação : normativo ou dialógico? - Sposito, Cinthya Cardozo da Silva (2011)
This study aimed to investigate why the educational process within the courses in the area of computing does not promote the right conditions for their people to act ethically. The reasons that lead us to this research are the offensive attitudes committed by many students of computing. Thus, the phenomenological method was used to describe, analyze, understand and interpret the educational process in the field of computing. We realize that there is efficacy of the educational process, as it is currently structured, since it is based on a curriculum that seeks to convey values and norms of behavior socially acceptable as well as provided by law, behavior, understanding that the mere fact that the student knows these codes will be enough that he has an ethical conduct. Therefore, it becomes necessary to restructure this education process in order to make it developer of dialogue that gives each person the space of authenticity and autonomy about their lives, their attitudes and how its existence brings implications for all other people. Namely, that the individual understands that every choice he makes, chooses for all mankind, and that, therefore, is responsible ethical and aesthetically with the independent exercise of their freedom, authentic and responsible.